A dynamic model of tablet film coating processes for control system design. (June 2023) - Rodrigues, Cecilia Pereira; Duchesne, Carl; Poulin, Éric; Lapointe-Garant, Pierre-Philippe
Highlights: New dynamic macro scale model of a tablet pan coater based on energy and mass transfer equations. Modeling for control system design and the development of system observers to estimate critical unmeasured variables in real-time. Model parametrization and calibration using pilot plant batch data. Model captures the main process variable trajectories, with errors below 2 °C for the outlet gas and tablet bed temperatures, and 2% for the outlet gas relative humidity. Abstract: Aqueous film coating is a common and important step in the production of most pharmaceutical tablets. Controlling this process is beneficial to maintain stable and optimal operation and the use of a model capable of describing its main physical phenomena is fundamental for control system design. This paper presents the development of a dynamic macro scale model of a pan coater based on energy and mass transfer equations. Model complexity is kept low to simplify parameterization and allow for real-time applications, such as the development of system observers to estimate critical unmeasured variables. Pilot plant data from seven batches, ran according to designed experiments, are used for model calibration and validation. The final model adequately captures the global trajectories of the main process variables; mean differences between experimental and simulated values are below 2 °C for the outlet gas and tablet bed temperatures, and 2% for the outlet gas relative humidity.